Developing multicultural leadership using knowledge dynamics and cultural intelligence - Paiuc, Dan (Emerald Publishing Limited, 2024)
In an increasingly multicultural workforce, leaders need to navigate and build upon cultural and societal differences. The work-from-anywhere phenomenon has conquered the globe, propelling multicultural leadership to the new standard in today's fast-paced and polycentric world. Combining organizational context, knowledge dynamics and cultural intelligence, chapters here provide guidance on how to lead effectively in a multicultural context and leveraging these global workforces to increase bottom-line results and improve employee satisfaction. Dan Paiuc helps both current and future managers and leaders navigate evolving multicultural leadership, building on academic and business research.
Keywords: Diversity in the workplace.; Leadership.; Business & Economics -- Leadership.; Management: leadership and motivation.; elektronické knihy; electronic books